Location of Back-shu Points of the Bladder Meridian in the Lumbar Region through Patient Measurement - Ho-Yun Sim; Sang Kyun Park; Kwang Ho Lee (MEDrang Inc., 2018)
Background The purpose of this study was to compare the first branch of the bladder meridian (FBBM) as determined by the proportional bone measurement method (PBMM), to the line formed by the erector spinae muscle group, and to establish an academic basis for selection of acupuncture points and needling. Methods Sixty participants were divided into 3 groups based on body mass index (BMI) and into 2 groups based on waist/height ratios. The distance from the midline of the spine to the first branch of the bladder meridian with PBMM (DFBBM), and the distance from the midline of the spine to the most elevated fleshy region of the erector spinae (DMEFR), at the same level as the inferior border of the spinous processes of L1-L5, were measured. The DFBBM and the 5 DMEFRs were then analyzed according to BMI and the waist/ height ratio. Results DFBBM was statistically different from DMEFR in all back-shu points in the lumbar region. DFBBM was not significantly different from DMEFR in the groups with a high BMI or waist/height ratio. However, there was a statistical difference in the groups with a low or moderate BMI or low waist/height ratio. Conclusions Since the location of the most elevated fleshy region of the erector spinae does not coincide with the location of the FBBM, the selection of back-shu points in the lumbar region must be performed precisely by PBMM.